Medieval Irish chronicles reveal persistent volcanic forcing of severe winter cold events, 431 - 1649 CE - Hennessy, Mark; Ludlow, Francis (My University, 2013)
Explosive volcanism resulting in stratospheric injection of sulfate aerosol is a major driver of regional to global climatic variability on interannual and longer timescales. However, much of our knowledge of the climatic impact of volcanism derives from the limited number of eruptions that have occurred in the modern period during which meteorological instrumental records are available. We present a uniquely long historical record of severe short-term cold events from Irish chronicles, 431?1649 CE, and test the association between cold event occurrence and explosive volcanism. Thirty eight (79%) of 48 volcanic events identified in the sulfate deposition record of the Greenland Ice Sheet Project 2 ice-core correspond to 37 (54%) of 69 cold events in this 1219 year period. We show this association to be statistically significant at the 99.7% confidence level, revealing both the consistency of response to explosive volcanism for Ireland?s climatically sensitive Northeast Atlantic location and the large proportional contribution of volcanism to historic cold event frequencies here. Our results expose, moreover, the extent to which volcanism has impacted winter-season climate for the region, and can help to further resolve the complex spatial patterns of Northern Hemisphere winter-season cooling versus warming after major eruptions
PUBLISHED
Mark Hennessy (Joint Author) Explosive volcanism resulting in stratospheric injection of sulfate aerosol is a major driver of regional to global climatic variability on interannual and longer timescales. However, much of our knowledge of the climatic impact of volcanism derives from the limited number of eruptions that have occurred in the modern period during which meteorological instrumental records are available. We present a uniquely long historical record of severe short-term cold events from Irish chronicles, 431?1649 CE, and test the association between cold event occurrence and explosive volcanism. Thirty eight (79%) of 48 volcanic events identified in the sulfate deposition record of the Greenland Ice Sheet Project 2 ice-core correspond to 37 (54%) of 69 cold events in this 1219 year period. We show this association to be statistically significant at the 99.7% confidence level, revealing both the consistency of response to explosive volcanism for Ireland?s climatically sensitive Northeast Atlantic location and the large proportional contribution of volcanism to historic cold event frequencies here. Our results expose, moreover, the extent to which volcanism has impacted winter-season climate for the region, and can help to further resolve the complex spatial patterns of Northern Hemisphere winter-season cooling versus warming after major eruptions.
Keywords: volcano-climate, palaeoclimate, temperature extremes, Ireland, Northeast Atlantic, ice-cores, medieval chronicles; volcano-climate, palaeoclimate, temperature extremes, Ireland, Northeast Atlantic, ice-cores, medieval chronicles; Making Ireland; Smart & Sustainable Planet; Agriculture, settlement and society in medieval Ireland; Annals; CLIMATE; CLIMATE CHANGE; CLIMATE-CHANGE; Chronicles; Climate Change; Climate Change Impacts on the Environment; Climate History; Early Medieval History; GLOBAL CLIMATE-CHANGE; HOLOCENE CLIMATE; Irish History; Late Medieval Ireland, 1166-1534; MEDIEVAL; Medieval History; Medieval History; Medieval Ireland; Medieval Ireland; Medieval Sources; Medieval Studies; PALAEOCLIMATE; PALEOCLIMATE; VOLCANIC ACTIVITY; Volcanic Aerosol; Volcanic Eruptions; climate change impacts; climate research; volcanic dust veil